Best techniques for endoscopic ampullectomy. Issue 5 (September 2020) - Klair, Jagpal S.; Irani, Shayan; Kozarek, Richard
Abstract : Purpose of review: Endoscopic ampullectomy has proven its safety and efficacy in multiple studies, making it the favorable option for the management of endoscopic ampullectomy. In this review, we plan to review the basic steps every endoscopist should be familiar with before undertaking endoscopic ampullectomy. Recent findings: In this review, we plan to discuss the indications, preresection evaluation process including endoscopic ultrasound, endoscopic ampullectomy techniques with side-viewing endoscope and endoscopist experience/comfort with the management of the endoscopic ampullectomy complications. Summary: Things of utmost interest include reviewing all the ampullary biopsy specimens by an expert gastrointestinal pathologist, careful preresection staging, en bloc resection, familiarity with tools and techniques of endoscopic ampullectomy, postresection adverse events & management and postprocedure surveillance.